SARS-CoV-2 IgG response in symptomatic and asymptomatic COVID-19-infected healthcare workers. (19th May 2021) - Cordova, E; Bacelar, B; Nieto, F; Garibaldi, F; Aguirre, V; Machuca, M; Badia, M; Rodriguez, C
Abstract: Background: Healthcare workers (HCWs) accounted for a significant proportion of COVID-19 infections worldwide. Retrospective seroprevalence surveys are often used to screen for unidentified previous infection with SARS-CoV-2. However, the rate of humoral response in HCWs affected by COVID-19 is not well-defined. Aims: To assess the specific IgG humoral response in symptomatic and asymptomatic SARS-CoV-2-infected HCWs and identify potential factors associated with humoral response. Methods: We prospectively recruited 204 HCWs with RT-PCR-confirmed COVID-19 infection to evaluate SARS-CoV-2 humoral response. Serum-IgG antibodies against SARS-CoV-2 were analysed using two commercially available serological assays. A logistic regression was performed to identify independent factors associated with positive IgG serology test. Results: Overall, the SARS-CoV-2 IgG seropositivity rate was 77%. This seropositivity rate was higher in symptomatic than in asymptomatic COVID-19 infection (83% versus 57%; P < 0.001) and in older HCWs.. The seropositivity rate did not diminish with time. In logistic regression, only a history of COVID-19 symptoms and age were identified as independent factors associated with the detection of anti-SARS-CoV-2 IgG antibodies. Conclusions: SARS-CoV-2 IgG antibodies are found significantly more frequently in symptomatic and in older HCWs. The fact that not all COVID-19 HCWs develop detectable IgG is vital for the interpretation of COVID-19 seroprevalence surveys.